THE ROLE OF HEALTH WORKERS IN HANDLING CHOKING IN INFANTS IN THE WORKING AREA OF THE KAYU LAUT HEALTH CENTER, SOUTH PENYABUNGAN DISTRICT, MANDAILING NATAL REGENCY, NORTH SUMATRA PROVINCE YEAR 2024 - Rizkiyah, Fitri; Herna Rinayanti Manurung; Juliana Munthe3; Monica Situngkir; Henny Rista; Mutia Pratiwi; Meniat Jaya (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
According to data released by the World Health Organization (WHO) in , there were 17,537 cases of children under five years old (1-3 years old) who experienced choking. The main causes of this occurrence were food (59.5%) and foreign objects (31.4%), while 9.1% of the causes were unknown. In addition, the death rate due to choking in the UK also showed an increase. The main cause of choking is food stuck in the throat. According to data from the Office for National Statistics, there were 289 choking deaths in 2016, which represents an increase of 17% compared to the previous year. In the United States, 34 children were admitted to the emergency room due to choking on food. An estimated 12,435 children under the age of 14 are being treated in hospitals in the United States. The cause is choking on food due to the choking of formula milk or breast milk, sweets, meat, bones, fruits and vegetables. This research method is observational/survey using questionnaires or questionnaires without intervention. The type of research is descriptive analytics with cross-sectional. : the majority of health workers with Bachelor’s Education were 16 people (48%) each and the minority of Diploma education was 3 people (9.0%). The majority of health workers were over 35 years old, with a total of 20 people or 61.0%. Meanwhile, health workers under the age of 35 amounted to 13 people or 39.0%. the majority of health workers have worked > 1 year as many as 26 people (79.0%) and minorities < 1 year as many as 7 people (21.0%). the majority of 18 people (55.0%) had 1 < training history and 15 people (45.0%) had a good or sufficient level of knowledge. Meanwhile, a small percentage of respondents, namely 8 people or 24.0%, have a lack of knowledge.